The Influence of Social Support on Mental Health Among Undergraduate Students - Ahmad, Anis; Kumari, Nidhi (Journal of Neonatal Surgery, 2025)
Mental health is a core dimension of overall well-being that shapes the academic progress, personal growth, and social adjustment of undergraduate students. The move into higher education often brings academic pressure, social change, and emotional strain, leaving students susceptible to psychological difficulty. Social support is widely regarded as a protective resource that builds resilience and supports positive mental health. This study examined how perceived social support relates to mental health among undergraduate students. A quantitative, cross-sectional, correlational design was used. Data were gathered from 360 undergraduate students between 16 and 25 years of age (M = 20.23, SD = 2.05), recruited through convenience sampling. Mental health was measured with the Mental Health Inventory (Prasad & Srivastava, 2003), and perceived social support was measured with the Social Support Questionnaire (Nehra, Kulhara, & Verma, 1998). Data were analysed in IBM SPSS using descriptive statistics, Pearson product-moment correlation, and multiple regression. Result revealed that there was positive and significant association between overall perceived social support and mental health (r = .209, p < .001). It was also found that Support from friends (r = .250, p < .001) and from significant others (r = .162, p = .002) were positively related to mental health. However, insignificant relationship was obtained between family support and mental health (.035, p>.05). Regression analysis was computed to measure the predictive effect of the three support dimensions of social support on mental health. The dimensions of social support scores accounted for 8.0% of the variance in mental health (R² = .080, F(3, 356) = 10.252, p < .001). The friend support emerged as the strongest predictor of mental health (β = .238, p < .001), followed by support from significant others (β = .146, p = .013). However, family support did not emerge significant predictor of the mental health. These results pointed out the importance of peer relationships and interpersonal networks for undergraduate psychological well-being. Findings suggested that colleges and universities would benefit from strengthening peer-support programmes, counselling services, and broader mental health promotion initiatives